Muhammad Iqbal's The Philosophy Khudi and Its Relevance to Contemporary Indonesia - Zulkarnain Zulkarnain (al-Lubb: Journal of Islamic Thought and Muslim Culture, 2019)
Muhammad Iqbal's The Philosophy Khudi and Its Relevance to Contemporary Indonesia